Design and Control of IoT Based Automatic Watering Devices for Vegetable Plants - Iriyanti, Aldarisma; Agung, Muhammad; Wahid, Abdul (Internet of Things and Artificial Intelligence Journal, 2025)
This research aims to design and develop an Internet of Things (IoT)--based automatic watering device for vegetable crops, especially water spinach and bok choy. The IoT technology used allows users to monitor and control the watering process remotely through an Android-based mobile application. The device is equipped with a soil moisture and temperature sensor (DHT22), which automatically controls the water pump and fan according to the needs of the plants. System testing was conducted to ensure the functionality of the sensors and that the automatic watering system operates effectively. The test results show that the device works efficiently in maintaining soil moisture and plant temperature, thereby improving the maintenance of vegetable crops. With this system, watering is done promptly and according to the needs of the plants, thereby reducing water and energy wastage. This research offers a practical solution for farmers or plant enthusiasts to monitor and care for plants automatically and efficiently.